2008
DOI: 10.1098/rstb.2007.2237
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the other metazoan body plans: the evolution of larval forms

Abstract: Bilaterian animal body plan origins are not solely about adult forms. Most animals have larvae with body plans, ontogenies and ecologies distinct from adults. There are two primary hypotheses for larval origins. The first hypothesis suggests that the first animals were small pelagic forms similar to modern larvae, with adult bilaterian body plans evolved subsequently. The second hypothesis suggests that adult bilaterian body plans evolved first and that larval body plans arose by interpolation of features into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 40 publications
(40 reference statements)
4
103
3
Order By: Relevance
“…This study revealed that in modern echinoids, changes to mesodermal GRN architecture have occurred more frequently than alterations to ectodermal GRN architecture. These results support the notion that GRN architecture evolves at different rates (81), and provide an in-principle explanation for the rapid evolution observed in both cidaroid and euechinoid sea urchin lineages that have convergently and independently evolved directdeveloping larval forms (53). It remains to be determined in future research whether the shared regulatory states between cidaroids and euechinoids elucidated here are the product of conserved stretches of genomic DNA hardwired in the cis-regulatory regions of orthologous regulatory genes or the result of diverged cis-regulatory modules producing similar developmental outcomes.…”
Section: Evolution Of Global Embryonic Domains In Early Development Ofsupporting
confidence: 82%
See 1 more Smart Citation
“…This study revealed that in modern echinoids, changes to mesodermal GRN architecture have occurred more frequently than alterations to ectodermal GRN architecture. These results support the notion that GRN architecture evolves at different rates (81), and provide an in-principle explanation for the rapid evolution observed in both cidaroid and euechinoid sea urchin lineages that have convergently and independently evolved directdeveloping larval forms (53). It remains to be determined in future research whether the shared regulatory states between cidaroids and euechinoids elucidated here are the product of conserved stretches of genomic DNA hardwired in the cis-regulatory regions of orthologous regulatory genes or the result of diverged cis-regulatory modules producing similar developmental outcomes.…”
Section: Evolution Of Global Embryonic Domains In Early Development Ofsupporting
confidence: 82%
“…Alterations to GRN architecture have occurred frequently throughout the network since their divergence. In addition, these results offer an in-principle explanation for the rapid changes in developmental processes during the convergent evolution of direct-developing, nonfeeding sea urchins (50)(51)(52)(53).…”
mentioning
confidence: 77%
“…An emerging research direction focuses on comparative studies of neuronal circuitry in diverse marine larvae. Even though the evolutionary origin and ancient versus modern origin of larvae is still debated [73,74], our results support the view that the larval eyes and brain of annelids (and probably other spiralian) represent more closely an ancestral stage of brain evolution [8]. Comparing circuits in spiralian larval nervous systems to the circuits of cnidarian larvae and the ciliated larvae of certain marine deuterostomes (e.g.…”
Section: Discussionsupporting
confidence: 80%
“…THE PROTOSTOME -DEUTEROSTOME TOOLKIT The similarity of a variety of complex morphogenetic pathways across protostomes and deuterostomes (based initially on studies of Drosophila, Cenorhabditis and Mus, but recently expanding to a more phylogenetically diverse array of animals) led to the conclusion that their last common ancestor not only possessed these developmental systems, but the complex morphologies that they produce in modern organisms (Slack et al 1993;De Robertis & Sasai 1996;Ohno 1996;Valentine et al 1999;Carroll et al 2001;Erwin & Davidson 2002;Erwin 2006;De Robertis 2008;Raff 2008). …”
Section: Introductionmentioning
confidence: 99%